Charakterystyka bezrobocia w Tarnowie i powiecie tarnowskim w latach 2005-2007 - Kozioł - Plucińska, Beata (My University, 2008)
W pracy zwrócono uwagę na bardzo ważny w dzisiejszym świecie problem bezrobocia, a terenem badań jest miasto Tarnów, a także Powiat Tarnowski. W pierwszej części opisano ogólnie zjawisko bezrobocia, jego rodzaje i koszty. Druga część poświęcona jest omówieniu aktywnych i pasywnych form przeciwdziałania bezrobociu. W trzeciej części scharakteryzowano Tarnów i Powiat Tarnowski jako ośrodek działań biznesowych, co ma znaczący wpływ na liczbę zatrudnionych na tym terenie osób. W tej części też zawarte są dane statystyczne dotyczące bezrobocia na analizowanym terenie w latach od: 2005- 2007. Dane te dotyczą nie tylko ogólnej liczby bezrobotnych w poszczególnych miesiącach, ale również struktury bezrobotnych.

The thesis was to present the problem of unemployment and its structure in Poland by analysing the situation of Tarnów and its nearby area. Another aim of the thesis was to show how the Tarnów’s Job agency prevents unemployment and what are the long-term programs which are to reduce and in fact do reduce, with notable effects, the unemployment. In Tarnów’s region in years 2005 to 2007 the unemployment was high. In 2005 it was the highest. The largest group of unemployed consisted of: graduates, poorly educated people, women and people between the age of 18 and 24. The percentage of unemployed dropped mainly due to dynamic programs of P.U.P in Tarnów. Currently the most important issue for Poland, which is now fully a member of the European Union, is preventing unemployment by conducting training programmes, public and intervention works, increasing the number of people active in the labour market, taking advantage of job offers offered by other countries of Europe and making use of all the opportunities given to our country by the European Union.
Characteristic unemployment in Tarnow city and the district of Tarnow in years 2005 to 2007
Keywords: bezrobocie; przeciwdziałanie bezrobociu; rynek pracy; powiat tarnowski; unemployment; preventing unemployment; labor market